456 Ten-Year Outcomes of Image-Guided Ablation and Partial Nephrectomy for T1 Renal Cell Carcinoma. (19th August 2022) - Chan, VWS; Osman, FH; Cartledge, J; Gregory, W; Kimuli, M; Vasudev, N; Ralph, C; Jagdev, S; Bhattarai, S; Smith, J; Lenton, J; Wah, TM
Abstract: Objective: This is the first study to compare 10-year oncological outcomes and peri-operative outcomes of IGA and PN in patients with confirmed small renal cell carcinomas (RCC). Method: This is a retrospective cohort study of localised RCC (T1a/bN0M0) patients undergoing cryoablation (CRYO), radio-frequency ablation (RFA) or laparoscopic PN at our institution from 2003 to 2016. Oncological outcomes were compared using Cox regression and log-rank analysis. eGFR changes were compared using Kruskal-Wallis and Wilcoxon-rank tests. Results: 296 (238 T1a, 58 T1b) patients were identified, 103, 100 and 93 patients underwent CRYO, RFA and PN, respectively. Median follow-up time was 75, 98 and 71 months, respectively. Patients undergoing PN are significantly younger and have fewer complex tumours than those undergoing CRYO or RFA (p<0.001). On univariate analysis, all oncological outcomes were comparable amongst CRYO, RFA and PN (p>0.05). On multivariate analysis, T1a patients undergoing RFA had improved local-recurrence-free survival (LRFS) (HR 0.002, 95%CI 0.00–0.11, p=0.003) and metastasis-free survival (HR 0.002, 95%CI 0.00–0.52, p=0.029) compared to PN. In T1a and T1b patients combined, both CRYO (HR 0.07, 95%CI 0.01–0.73, p=0.026) and RFA (HR 0.04, 95%CI 0.03–0.48, p=0.011) had improved LRFS rates. Patients undergoing CRYO and RFA had a significantly smaller median decrease in eGFR post-operatively compared to PN (T1a: p<0.001; T1b: p=0.047). Limitations include retrospective design and limited statistical power. Conclusions: IGA is potentially as good as PN in oncological durability. IGA preserves kidney function significantly better than PN. More studies with larger sample size should be performed to establish IGA as a first-line treatment alongside PN.